Binding and neutralizing anti-cytomegalovirus activities in immune globulin products. (November 2017) - Wang, Xiao; Xu, Yanqun; Scott, Dorothy E.; Murata, Haruhiko; Struble, Evi B.
Abstract: Congenital infection as well as infection of immunocompromised individuals by cytomegalovirus (CMV) can be associated with significant morbidity, mortality, and long-term adverse health outcomes. Assessment of anti-viral activity using appropriate assays is essential for ensuring safe and efficacious use of therapeutic CMV immune globulin (IG) products. In this study, we used commercial ELISA kits to compare anti-CMV antibody binding activity and avidity for lots of CMV-specific and normal IG products available in the US market. Additionally, neutralizing activity of IG products was measured against CMV strains (AD169 wt131 or TB40E-GFP) in MRC-5 human fibroblasts and ARPE-19 human epithelial cells. Our data revealed that, regardless of the method, anti-CMV activity was higher in CMV IG lots we tested compared with normal IG lots; CMV binding activity was at least 4-fold higher, and neutralizing activity at least 2- and 3-fold higher for epithelial and fibroblast cells, respectively, in CMV IG lots compared with normal IG lots. Furthermore, anti-CMV activity values from all three methods (ELISA, neutralization in MRC-5 cells, and neutralization in ARPE-19 cells) were highly correlated, whereas avidity, although higher in CMV IG lots, did not correlate well with either binding or neutralizing activities.